Coordination self-assembly through weak interactions in meso-dialkoxyphosphoryl-substituted zinc porphyrinates. Issue 16 (4th April 2019) - Nefedov, Sergey E.; Birin, Kirill P.; Bessmertnykh-Lemeune, Alla; Enakieva, Yulia Y.; Sinelshchikova, Anna A.; Gorbunova, Yulia G.; Tsivadze, Aslan Y.; Stern, Christine; Fang, Yuanyuan; Kadish, Karl M.
Abstract : Non-coordinating aryl substituents determine the organization of zinc meso -(diethoxyphosphoryl)diarylporphyrins in crystals and in solution. Abstract : The self-assembly of seven zinc 10-(dialkoxyphosphoryl)-5, 15-diarylporphyrinatesZn5–Zn11 containing different substituents at the phosphonate and aryl groups was investigated. Single crystals ofZn5–Zn9 complexes were grown under the same conditions and analyzed by X-ray structural analysis. A supramolecular self-assembly is observed in all crystals through weak coordinative bonding of the phosphoryl group of one porphyrin molecule to the zinc(ii ) ion of a second molecule. The geometry of the porphyrin macrocycle is similar in all of the studied crystals and the central zinc atom in each case adopts a distorted tetragonal pyramidal environment. However, theZn5–Zn7 porphyrins display a 1D polymeric structure while theZn8 andZn9 complexes exist as discrete cyclotetramers in the crystals. This data demonstrates that the non-coordinating meso -aryl substituents of meso -(dialkoxyphosphoryl)porphyrins influence their crystalline organization. A self-assembly of theZn5–Zn11 complexes is also observed in toluene and chloroform solutions over a large temperature range (223–323 K). According to NMR studies, the associates exhibit dynamic behavior. A well-defined supramolecular aggregate of complexZn10 at 10 −3 M in toluene and chloroform solutions was unambiguously characterized as a cyclotetramer[Zn10]4 by 1 H NMR spectroscopy at 223 K. The structure of theZn10 association in toluene and chloroform shows a concentration dependence. When a solution ofZn10 in toluene was diluted from 10 −3 M to 10 −5 M, the average number of molecules in the associated unit decreased to about two.